Reação de diferentes culturas a Monosporascus cannonballus - Balbino, Deyse Anne Dias (Universidade Federal Rural do Semi-Árido, 2015)
The fungus M. cannonballus is a thermophilic plant pathogen, associated with the decline of crude oil in cucurbits worldwide. Although frequently associated with this family, which causes the decline of crude oil, this fungus has been reported in other crops, including maize, beans and cotton, and is, however, little known pathogenicity in these species. The objective of this study was to evaluate the susceptibility of cultivars of different host crops cucurbits and not cucurbits, front inoculation of two isolates of M. cannonballus. The present study tested the behavior of two isolates of M. cannonballus, CMM 3646, isolated Boerhavia diffusa roots (Catch pinto) and CMM 2390, isolated from melon roots, compared to 10 crops (tomatoes, beans, sesame, pumpkin, cucumber, melon, watermelon, sorghum, corn and cotton) with two cultivars of each, totaling forty treatments. With the means of this evaluation we calculated the overall index of the disease (IGD). Pathogenicity was confirmed by isolation of the inoculated fungus. The production of the inoculum of strains was made from the PDA culture medium containing the fungus mycelium. The crops were grown in pots containing sterile soil mixture, sand and substrate. After 50 days of culture, the insulation made from the roots of plants. It was found varying degrees of resistance and susceptibility of cultivars evaluated on isolates used. Cultivars of cucurbits were grouped into categories which the highly susceptible front of the CMM-3646 and CMM-2390 isolated. The species belonging to this family were the ones that had higher IGD. The cultivars of tomato and corn had susceptibility behavior to fungal isolates of M. cannonballus. The sorghum cultivars for both isolates of M. cannonballus behaved as moderately resistant. The cultures do not cucurbits such as cotton, sesame and cowpea obtained degrees of resistance to the fungal isolates used
Different cultures of reaction the M. cannonballus
Keywords: Fungos; Patógeno radicular; Monosporascus cannonballus; Fungi; Root pathogen; Monosporascus cannonballus; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA